12+2k=2(k+6)

Simple and best practice solution for 12+2k=2(k+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12+2k=2(k+6) equation:



12+2k=2(k+6)
We move all terms to the left:
12+2k-(2(k+6))=0
We calculate terms in parentheses: -(2(k+6)), so:
2(k+6)
We multiply parentheses
2k+12
Back to the equation:
-(2k+12)
We get rid of parentheses
2k-2k-12+12=0
We add all the numbers together, and all the variables
=0
k=0/1
k=0

See similar equations:

| 5rr=6 | | -7m+14=70 | | -7x+3x–9x=12x–5 | | 101.1x+1.2x−5.4=−10 | | y=9.00(1.015)^20 | | -8x-(8x)=48 | | 12/27=x/(x+5) | | y=34,000(1.025)^5 | | 13n+4(n+9)=104 | | 16y2+24y=-9 | | 3x31=93 | | y=500(1.05) | | 3/4f+21=18 | | 3x-18x=8 | | 6.7x-13.5=26.7 | | 4/5​(20m−5)=−72−m | | 216^{3x+3}=1296^{2x+5} | | 2t^2-3t-16=0 | | 12+s=15s= | | 2m+1=–7 | | 30.1÷x=7 | | 11^x+4=9 | | 2÷x=15 | | 5p=110 | | 3x-9=12(x-3) | | 4x+7=-5x-8 | | 3t2+4t+7=0 | | 30u=120 | | 75=t-14 | | 75=t−14 | | 82×.80+.20x=80 | | 5(2-7x)=95 |

Equations solver categories